Proliferin-1 Ameliorates Cardiotoxin-Related Skeletal Muscle Repair in Mice - Hiroki Goto; Aiko Inoue; Limei Piao; Lina Hu; Zhe Huang; Xiangkun Meng; Yusuke Suzuki; Hiroyuki Umegaki; Masafumi Kuzuya; Xian Wu Cheng (Hindawi Limited, 2021)
Background. We recently demonstrated that proliferin-1 (PLF-1) functions as an apoptotic cell-derived growth factor and plays an important role in vascular pathobiology. We therefore investigated its role in muscle regeneration in response to cardiotoxin injury. Methods and Results. To determine the effects of PLF-1 on muscle regeneration, we used a CTX-induced skeletal muscle injury model in 9-week-old male mice that were administered with the recombinant PLF-1 (rPLF-1) or neutralizing PLF-1 antibody. The injured muscles exhibited increased levels of PLF-1 gene expression in a time-dependent manner. On day 14 after injury, rPLF-1 supplementation ameliorated CTX-induced alterations in muscle fiber size, interstitial fibrosis, muscle regeneration capacity, and muscle performance. On day 3 postinjury, rPLF-1 increased the levels of proteins or genes for p-Akt, p-mTOR, p-GSK3α/β, p-Erk1/2, p-p38MAPK, interleukin-10, Pax7, MyoD, and Cyclin B1, and it increased the numbers of CD34+/integrin-α7+ muscle stem cells and proliferating cells in the muscles and/or bone marrow of CTX mice. An enzyme-linked immunosorbent assay revealed that rPLF-1 suppressed the levels of plasma tumor necrosis factor-α and interleukin-1β in CTX mice. PLF-1 blocking accelerated CTX-related muscle damage and dysfunction. In C2C12 myoblasts, rPLF-1 increased the levels of proteins for p-Akt, p-mTOR, p-GSK3α/β, p-Erk1/2, and p-p38MAPK as well as cellular functions; and these effects were diminished by the depletion of PLF-1 or silencing of its mannose-6-phosphate receptor. Conclusions. These findings demonstrated that PLF-1 can improve skeletal muscle repair in response to injury, possibly via the modulation of inflammation and proliferation and regeneration, suggesting a novel therapeutic strategy for the management of skeletal muscle diseases.